2017
DOI: 10.1038/srep40373
|View full text |Cite
|
Sign up to set email alerts
|

Food-grade TiO2 impairs intestinal and systemic immune homeostasis, initiates preneoplastic lesions and promotes aberrant crypt development in the rat colon

Abstract: Food-grade titanium dioxide (TiO2) containing a nanoscale particle fraction (TiO2-NPs) is approved as a white pigment (E171 in Europe) in common foodstuffs, including confectionary. There are growing concerns that daily oral TiO2-NP intake is associated with an increased risk of chronic intestinal inflammation and carcinogenesis. In rats orally exposed for one week to E171 at human relevant levels, titanium was detected in the immune cells of Peyer’s patches (PP) as observed with the TiO2-NP model NM-105. Dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
353
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(400 citation statements)
references
References 55 publications
14
353
0
5
Order By: Relevance
“…Due to the ubiquitous role of metal elements for cellular functions, a significant change in the household of these elements could lead to incalculable long term effects on the cell level as well as on the organism level. Long term effects of TiO 2 NMs and E171 on rats were already shown . On the one hand, it was claimed that an acute exposure of one week to rats led to an accumulation of TiO 2 in peyer's patches, but did not induce instestinal inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the ubiquitous role of metal elements for cellular functions, a significant change in the household of these elements could lead to incalculable long term effects on the cell level as well as on the organism level. Long term effects of TiO 2 NMs and E171 on rats were already shown . On the one hand, it was claimed that an acute exposure of one week to rats led to an accumulation of TiO 2 in peyer's patches, but did not induce instestinal inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Following an in-depth re-evaluation of this compound based on the data available in early 2016, the European Food Safety Agency had no scientific reason to reject this inorganic compound as a food additive. Scientific questions that have yet to be answered include the impact of such particles from long-term exposure (as in work developed by Bettini et al (2017)) and the fate of the non-excreted fraction (location, clearance, effect) as well as its nanoparticle content. Given the demonstrated differences between E171 and P25 materials, we strongly urge researchers studying the biological effects of ingested TiO2 to consider the food-grade forms in addition to P25 forms.…”
Section: Resultsmentioning
confidence: 99%
“…In rats, nano‐TiO 2 (10 mg/kg bw/day, 7 days, gavage) was shown to increase dendritic cells frequency in Peyer's patches but not in the spleen. No intestinal inflammation was reported, and no ( in vivo ) or limited ( in vitro ) effects were observed on Treg and Th cell subsets . All other studies were performed in mice.…”
Section: Toxicitymentioning
confidence: 98%
“…Some rodent studies showed nano‐TiO 2 toxicity at several levels: immune system, central nervous system, kidneys, liver, spleen and fertility …”
Section: Toxicitymentioning
confidence: 99%